Features Of Competitive Strategy Development In Textile Enterprises (Czech Journal of Multidisciplinary Innovations, 2024)
The essence of response strategy and the conceptual foundation of its development, market viability and the primary determinants influencing it are studied in the article. Methodological issues of assessing the competitive potential of textile enterprises are covered. The main directions of competitive strategies of textile enterprises, as well as actionable suggestions on minimizing expenses via systematic resource management of resources in textile enterprises, have been developed